Designs for an anthropology of the contemporary. - Rabinow, Paul (Anthropology ; Social theory, 2008)
In this compact volume two of anthropology’s most influential theorists, Paul Rabinow and George E. Marcus, engage in a series of conversations about the past, present, and future of anthropological knowledge, pedagogy, and practice. James D. Faubion joins in several exchanges to facilitate and elaborate the dialogue, and Tobias Rees moderates the discussions and contributes an introduction and an afterword to the volume. Most of the conversations are focused on contemporary challenges to how anthropology understands its subject and how ethnographic research projects are designed and carried out. Rabinow and Marcus reflect on what remains distinctly anthropological about the study of contemporary events and processes, and they contemplate productive new directions for the field. The two converge in Marcus’s emphasis on the need to redesign pedagogical practices for training anthropological researchers and in Rabinow’s proposal of collaborative initiatives in which ethnographic research designs could be analyzed, experimented with, and transformed.